Effects of Xuefu Zhuyu Decoction on Cell Migration and Ocular Tumor Invasion in Drosophila. (25th April 2020) - Wang, Sitong; Wu, Fanwu; Ye, Bin; Zhang, Shiping; Wang, Xingjun; Xu, Qian; Li, Guowang; Zhang, Menglong; Wang, Shuai; Jia, Yongsen; Jiang, Chunhua; La, Xiaojin; et al.
Abstract : Xuefu Zhuyu Decoction (XFZYD), a Traditional Chinese Medicine (TCM) decoction mainly for treating blood stasis syndrome, has been widely investigated and applied in clinic and in laboratory. XFZYD contains 11 herbs and has been identified to promoting blood circulation to remove blood stasis for cardiovascular disease. Meanwhile, blood stasis is directly related to malignant tumor according to TCM basic theory. However, the effects of XFZYD on tumor metastasis and the underlying mechanisms are still largely unknown. Here, we employed well-established Drosophila cell migration and tumor invasion models to explore whether XFZYD has the anticancer activity on tumor metastasis in vivo . Our work has demonstrated that XFZYD could suppress cell migration and tumor invasion at the moderate concentrations. In addition, XFZYD altered the expression of MMP1, β -integrin, and E-cadherin to impede cell migration. Moreover, XFZYD inhibited ocular tumor invasion presumably by reducing the activity of Notch signaling. Together, these evidences reveal a positive role of XFZYD in suppressing cell migration and tumor metastasis, providing the potential drug targets and key clues for cancer clinical treatment strategies.